The Land Has Memory : Indigenous Knowledge, Native Landscapes, and the National Museum of the American Indian - Thrasher, Tanya; Blue Spruce, Duane (Book collections on Project MUSE., 2008)
In the heart of Washington, D.C., a centuries-old landscape has come alive in the twenty-first century through a re-creation of the natural environment as the region's original peoples might have known it. Unlike most plantings that surround other museums on the National Mall, the landscape around the Smithsonian's National Museum of the American Indian (NMAI) is itself a living exhibit, carefully created to reflect indigenous ways of thinking about the land and its uses. Abundantly illustrated, The Land Has Memory offers beautiful images of the museum's natural environment in every season as w.